2020
DOI: 10.3390/antibiotics9060282
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multiplex Polymerase Chain Reaction Assay on the Clinical Management of Adults Undergoing a Lumbar Puncture for Suspected Community-Onset Central Nervous System Infections

Abstract: Patients admitted from the community with a suspected central nervous system (CNS) infection require prompt diagnostic evaluation and correct antimicrobial treatment. A retrospective, multicenter, pre/post intervention study was performed to evaluate the impact that the BioFire® FilmArray® meningitis/encephalitis (ME) panel run in-house had on the clinical management of adult patients admitted from the community with a lumbar puncture (LP) performed for a suspected CNS infection. The primary outcome was the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Standard microbiological identification techniques, followed by antimicrobial susceptibility testing, and then followed by PCR identification of the resistance genes of concern is a tedious process that requires several days. This delay exposes the patients to the unnecessary adverse effects of the drugs, as well as extending the hospital stay for complicated cases, which increases the risk that the patients contract a hospital-acquired infection [ 56 ]. It is extremely important to implement rapid techniques that allow the identification of the causative pathogens within a few hours.…”
Section: Discussionmentioning
confidence: 99%
“…Standard microbiological identification techniques, followed by antimicrobial susceptibility testing, and then followed by PCR identification of the resistance genes of concern is a tedious process that requires several days. This delay exposes the patients to the unnecessary adverse effects of the drugs, as well as extending the hospital stay for complicated cases, which increases the risk that the patients contract a hospital-acquired infection [ 56 ]. It is extremely important to implement rapid techniques that allow the identification of the causative pathogens within a few hours.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that the use of FilmArray ME panel for adults suspected with central nervous system infection reduced the hospital length of stay (DiDiodato and Bradbury 2019; Moffa et al . 2020) and total antimicrobial days of therapy (Moffa et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020) and total antimicrobial days of therapy (Moffa et al . 2020). We retrospectively investigated cases of false‐positive, real‐time PCR‐based diagnoses using the FilmArray ME panel in our laboratory to measure the impact of using a dedicated biosafety cabinet (Mephilab; POCRAMé, Marseille, France) without airflow to reduce the prevalence of false‐positive diagnoses due to pre‐analytical in‐laboratory contamination.…”
Section: Introductionmentioning
confidence: 99%
“…One prior retrospective pre-post study of 97 total patients found no difference in the total duration of antibiotic therapy or hospital length of stay [ 9 ]. However, Moffa et al [ 10 ] found in a retrospective pre-post study of 160 patients hospitalized with a suspected community-acquired CNS infection that the total duration of antimicrobial therapy was significantly decreased by a median of 2 days, and hospital length of stay was significantly reduced by a mean of 2.2 days. However, in this study, antimicrobial therapy was still continued for a median of 5 days post-ME panel implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies have evaluated its diagnostic performance and clinical implementation in diagnostic pathways, few prior studies have assessed the impact of the multiplex PCR ME panel on the duration of empiric antibiotic therapy and time to targeted therapy, both of which have implications for patient safety and antibiotic stewardship [ 9 , 10 ]. The objective of our study was to evaluate the clinical impact of the multiplex PCR ME panel on the duration of empiric antibiotic therapy for suspected bacterial meningitis.…”
mentioning
confidence: 99%